How to follow-up a patient who received tocilizumab in severe COVID-19: a case report - Regina B. Podlasin; Justyna D. Kowalska; Andrzej Pihowicz; Beata Wojtycha-Kwaśnica; Magdalena Thompson; Tomasz Dyda; Hanna Czeszko-Paprocka; Andrzej Horban (European Journal of Medical Research, 2020)
Abstract Background COVID-19 is characterized by fast deterioration in the mechanism of cytokine storm. Therefore, treatment with immunomodulating agents should be initiated as soon as hyperinflammation is established. Evidence for the use of tocilizumab (TCZ) in COVID-19 is emerging, but the drug in this setting is used “off label” with limited data on both effectiveness and safety. Therefore, Hospital for Infectious Diseases in Warsaw established a Standard Operating Procedure (SOP) for the use of TCZ in severe COVID-19 cases. Case presentation Here, we present a case of 27-year-old, otherwise healthy man, who was successfully treated with chloroquine, azithromycin, tocilizumab and a standard of care. Initially the magnitude of lung devastation, clinical deterioration and the need for mechanical ventilation suggested unfavorable prognosis. However, we observed complete regression in radiological changes and rapid clinical improvement. Irrespective of this, patient’s serum interleukin 6 and aminotransferases remained elevated even after a month from treatment. Conclusions An overlapping effect of hyperinflammation, hypoxic organ injury and drug-related toxicity warrants a long-term follow-up for COVID-19 survivors. In addition, residual IL-6 receptors blockage may mask new infections. A standardized approach to follow-up for COVID-19 survivors is urgently needed. Current and future research should also investigate the impact of experimental therapies on lung tissue healing and regeneration, as well as long-term treatment toxicities.